2018
DOI: 10.18512/1980-6477/rbms.v17n2p177-189
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho Agronômico De Genótipos De Milho Submetidos Ao Estresse Hídrico No Sul Do Estado Do Tocantins

Abstract: RESUMO - A cultura do milho apresenta sensibilidade à variação climática, sendo o déficit hídrico uma das causas frequentes de redução de produção na cultura. O presente trabalho teve como objetivo avaliar a performance de genótipos de milho sob estresse hídrico, no sul do Estado do Tocantins. O experimento foi implantado no município de Gurupi - TO, utilizando 64 híbridos de milho. O delineamento experimental utilizado foi Látice 6x6, com três repetições. As características avaliadas foram altura da planta, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…Plants under irrigated conditions grew more, being around 2.37 m tall, while plants under water stress were on average 2.07 m tall, that is, under stress there was an average reduction of 30 cm in plant height. Melo et al (2018), studying maize genotypes subjected to water deficit during the tasseling period, also found lower PH compared to genotypes grown in environment without water deficit. A similar result was also observed for ear height, as there was a reduction of 15 cm in the main ear height in plants under water stress.…”
Section: Resultsmentioning
confidence: 89%
“…Plants under irrigated conditions grew more, being around 2.37 m tall, while plants under water stress were on average 2.07 m tall, that is, under stress there was an average reduction of 30 cm in plant height. Melo et al (2018), studying maize genotypes subjected to water deficit during the tasseling period, also found lower PH compared to genotypes grown in environment without water deficit. A similar result was also observed for ear height, as there was a reduction of 15 cm in the main ear height in plants under water stress.…”
Section: Resultsmentioning
confidence: 89%
“…In order to select the superior genotypes in this experiment, the following traits were utilized: flowering interval (FI), ear weight (EW), yield (YIE), prolificacy (Pr), and total chlorophyll index (TCI R6), for decision making in this research since, in breeding programs, the EW, YIE, and Pr traits are the most relevant, and the FI and TCI R6 traits are secondary traits, which have been used by maize breeders for to improve drought tolerance (CAMERA et al, 2007;SILVA et al, 2010;MELO et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The mean value obtained in the variable ear weight was of 1.97 kg, and in the variable yield, the mean value of 4649.74 kg/ha -1 was reported, which is already above the yield of the state of Espírito Santo, which is of 2,896 kg/ha -1 (CONAB, 2018), even the experiment being under water deficit. Evaluating the performance of maize genotypes under water stress, Melo et al (2018) reported a value of 4823.4 kg/ha -1 for yield. KASSIE et al (2017) reported that ;although, farmers normally considered yield of crop varieties when making adoption decisions, they also take into consideration the suitability of such varieties to the conditions of the local environment, particularly when they live in drought prone environments.…”
Section: Resultsmentioning
confidence: 99%
“…The productive performance of maize is influenced by several abiotic factors that occur simultaneously or at different stages of crop development. Recurrent water stress and low soil fertility are among the main causes of abiotic stresses that limit maize agronomic performance (Melo, Santos, Varanda, Cardoso, & Dias, 2018;Song, Jin, & He, 2019). With the increase in the maize area cultivated in the off-season (Companhia Nacional de Abastecimento [CONAB], 2023), it is expected that the crop will be even more exposed to abiotic stress conditions, such as water deficit, low incidence of solar radiation and variations in air temperature, especially during the final stage of development.…”
Section: Introductionmentioning
confidence: 99%